Developing EFL Learners’ Ability in Writing Report Text through Mind Mapping Technique - Aisyah Azahra; Tika Santika; Maya Rahmawati (Jurnal Ilmiah Profesi Pendidikan, 2022)
Mind mapping technique is one of the techniques that are very helpful in writing activities and is considered effective and able to help develop the ability of EFL learners in writing report text. This study aims to describe the development of the ability of EFL learners in writing report text through mind mapping technique. The research method in this study is qualitative research with a library research approach, where the researcher collects, analyzes, and reviews scientific journals or previous studies, which are then described and made a conclusion. The results showed that mind mapping was able to help in developing the ability of EFL learners in writing report text, especially in the content aspect, also mind mapping technique is considered very effective in helping to teach writing. Thus, it can be concluded that developing the ability of EFL learners in writing report text through mind mapping technique is very useful and effective in its use. So this study suggests EFL teachers be able to implement mind mapping technique in writing report text.